Diversity of UV Reflection Patterns in Odonata - Futahashi, Ryo (Frontiers in Ecology and Evolution, 2020)
Dragonflies and damselflies (Odonata) are large-eyed diurnal insects that exhibit a variety of color patterns on their wings and/or bodies. Because Odonata can perceive light with wavelengths extending from ultraviolet (UV) to red, the color patterns with UV reflection can be visually recognized by each other. The UV reflection patterns of Odonata have been investigated by using a UV camera and optically measuring the reflectance of body and wing surfaces. The UV reflection of Odonata can be classified into three classes, namely iridescent UV reflection, wax-based UV reflection, and UV reflection by epidermal granules. In this review, I present UV images of these three classes and representative examples of reflectance. Among the Odonata with colorful iridescent wings consisting of multilayer structures, some species (e.g., Chalcopteryx scintillans) predominantly reflect UV light, whereas other species (e.g., Calopteryx japonica) mostly reflect light at wavelengths above 400 nm. Whitish wax (called pruinescence) on the body and/or wing surface strongly reflect light including UV, due to the light-scattering fine structures produced by the wax. The chemical composition of the dragonfly’s abdominal UV-reflective wax differs from previously identified waxes of other organisms. The blue-tailed damselflies Ischnura species exhibit immature-adult-specific UV reflection by the pteridine pigment-based selective light scattering and absorption. Iridescent coloration and wax-based color changes are generally important for mate recognition and male-male competition in Odonata, although the ecological importance of UV reflection remains largely unknown except for few examples in damselflies.